Space of ω-Periodic Limit Functions and Its Applications to an Abstract Cauchy Problem - Rui Xie; Chuanyi Zhang (Journal of Function Spaces, 2015)
We introduce a new space consisting of what we call ω-periodic limit functions. We investigate some properties of the new function space. In particular, we study inclusion relations among asymptotically periodic type function spaces. Finally, we apply the ω-periodic limit functions to investigate the existence and uniqueness of asymptotically ω-periodic mild solutions of an abstract Cauchy problem.